Shift of wear balance acting on CVD textured coatings and relation to workpiece materials. (January 2021) - Bejjani, R; Odelros, S; Öhman, S; Collin, M
Innovative textured alumina coatings have been engineered to boost the performance of cutting tools. Different workpiece materials affect the wear inside the CVD textured alumina coating differently on the crater and flank side of the tools. How the balance in wear changes between the crater and flank side of the tool inside the alumina is not fully understood. Furthermore, any changes in steel elements in the workpiece can affect this balance differently. In this work, the wear of alumina coating has been studied after turning different workpiece materials (low alloy steel with and without Ca, ball bearing steel and stainless steel). The worn surfaces of the inserts were studied and their features related to the different materials. It was found that after machining under similar conditions, each workpiece material leaves a different signature, or worn surface, with unique features in the alumina coating layer. The transition between the sliding to the sticking region was studied in order to help understand the relation to wear when machining different workpiece materials. SEM and topography characteristics were identified on worn surfaces of the coated tools. The resulting worn volume and surface characteristics were related to different wear mechanisms acting on the rake and flank sides of the tool. This work studies the shift in balance between crater and flank wear by identifying different wear mechanisms acting inside the same alumina coating layer when machining different grades of steel. Such work can be a good resource for FEM wear modeling, where good simulation models must take into consideration the physics lying behind the wear types acting on each side of the tool.